Italian organized crime since 1950 - Catino, Maurizio (Crime and justice, 2020)
Italian mafias - Cosa Nostra, Camorra, and ‘Ndrangheta - are long-lived, resilient organizations that have evolved to adapt to environmental changes. They have different organizational models. While Cosa Nostra (in the past) and ‘Ndrangheta are characterized by a unitary, vertical structure and higher-level coordination bodies, Camorra has a plurality of organizational models; the majority of clans maintain a structure that is fluid, polycentric, and conflictual. In general, mafias with a vertical organizational order have greater control over conflict, and greater capacity to resist state power. The ‘Ndrangheta has become the richest and most powerful of the three, replacing Cosa Nostra in international drug trafficking. It is able to reproduce its organizational structures and business model in new territories in Italy and elsewhere. In contrast, owing to unprecedented law enforcement efforts in recent decades, Cosa Nostra is weaker, down but not out. Camorra continues to be the most violent mafia, committing more homicides than the other two combined. Consistent with their adaptive capacity, mafias in new areas of expansion are treated as novel agents that can provide extralegal services and business opportunities. They are sought out by entrepreneurs, white-collar professionals, and local politicians to solve problems such as debt collection, labor unrest, and disputes with suppliers.